2015
DOI: 10.1515/oere-2015-0029
|View full text |Cite
|
Sign up to set email alerts
|

Background donor concentration in HgCdTe

Abstract: Studies of background donor concentration (BDC) in HgCdTe samples grown with different types of technology were performed with the use of ion milling as a means of eliminating the compensating acceptors. In bulk crystals, films grown with liquid phase epitaxy and films fabricated with molecular beam epitaxy (MBE) on Si substrates, BDC of the order of ~10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…showed that it was possible to use this technique to determine the concentration of residual donors, an important parameter of the material that could not be measured using the conventional Hall-effect measurements due to electrical compensation [81]. Moreover, by creating a HgI concentration exceeding the equilibrium value by six to seven orders of magnitude, the etching can somehow activate even neutral defects in MCT [29].…”
mentioning
confidence: 99%
“…showed that it was possible to use this technique to determine the concentration of residual donors, an important parameter of the material that could not be measured using the conventional Hall-effect measurements due to electrical compensation [81]. Moreover, by creating a HgI concentration exceeding the equilibrium value by six to seven orders of magnitude, the etching can somehow activate even neutral defects in MCT [29].…”
mentioning
confidence: 99%